Continuous norming in learning progress monitoring—An example for a test in spelling from grade 2–4 - Schurig, Michael; Blumenthal, Stefan; Gebhardt, Markus (Frontiers in Psychology, 2022)
One of the main goals of the teacher and the school system as a whole is to close learning gaps and support children with difficulties in learning. The identification of those children as well as the monitoring of their progress in learning is crucial for this task. The derivation of comparative standards that can be applied well in practice is a relevant quality criterion in this context. Continuous normalisation is particularly useful for progress monitoring tests that can be conducted at different points in time. Areas that were not available in the normalization sample are extrapolated, closing gaps in applicability due to discontinuity. In Germany, teachers participated in a state-funded research project to formatively measure their children's spelling performance in primary school. Data (N=3000) from grade two to four were scaled, linked and translated into comparative values that can be used in classrooms independently from specific times. The tests meet the requirements of item response models and can be transferred well to continuous norms. However, we recommend using the 10th or 20th percentile as cut-off points for educational measures, as the 5th percentile is not discriminating enough.